Staphylococcus aureus cap5O and cap5P Genes Functionally Complement Mutations Affecting Enterobacterial Common-Antigen Biosynthesis in Escherichia coli - Kiser, Kevin B. (American Society for Microbiology, 1998)
The Staphylococcus aureus cap5P and cap5O genes of the type 5 capsule biosynthetic locus restore enterobacterial common-antigen expression to Escherichia coli mutants defective in rffE and rffD gene expression, respectively. Cap5P and Cap5O likely function as UDP-GlcNAc 2-epimerase and UDP-ManNAc dehydrogenase enzymes, respectively, in the synthesis of the capsule precursor UDP-ManNAcA.